COMPARISON ANALYSIS BETWEEN MALE AND FEMALE OF CONSUMER PURCHASE BEHAVIOR OF YAMAHA MIO - Pakasi, Alfa; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Humans have many needs and wants that they must fulfill in his life. Motorcycles is one requirement that must be met to be used as a means of transportation. Male and female have their own criteria for selecting the type of motorcycle they want. Male and female have different decision-making to buy a motorcycle. The method used in this research is the method of comparative data, collecting data through questionnaires, data analysis methods (validity and reliability), hypothesis testing and independent sample t-test. The results showed a significant difference between male and female in the purchasing behavior of consumers towards Yamaha Mio. Yamaha Mio sellers should consider offering their products for men and women differently. Keywords: decision making, consumer purchase behavior